Influence of vibration on grain size and degree of grain refinement in mild steel weldments - Tewari S.P. (My University, 2025)
Mild steel plates were welded under stationary and dynamic (longitudinal and transverse vibration) conditions. The frequency and amplitude ranges selected were 0 Hz to 300 Hz and 0 μm to 30 μm, respectively. It has been observed on the basis of experimental findings that vibration, in general, reduces the grain size of the weldment, and this reduction is appreciable at a lower amplitude of vibration. This may be due to the lower energy required for nucleation of the solid phase. Fast removal of latent heat of solidification from the solid liquid interface plays a significant part in the grain refinement under vibration. © 1993, Materials Research Society. All rights reserved.